Aligning teaching methods to learning outcomes at Can Tho University: Perspectives of undergraduate students - Thi Thuy Diem Huynh; Nhat Thao Kieu Nhien Nguyen; Thinh Mai Phuc; Van Nhuong Le; Anh Huy Huynh; Minh Quang Dinh (CTU Journal of Innovation and Sustainable Development)
This study investigates the effectiveness of common teaching methods (TMs) in meeting learning outcomes (LOs) at Can Tho University (CTU) from the students' perspective. A survey was conducted among 373 students across 13 training units to assess their perceptions of the alignment between LOs and TMs. The survey included questions on students' understanding of LOs, the role of lecturers in achieving LOs, and the effectiveness of various TMs in developing specialized knowledge, skills, soft skills, and character. Data were analysed using Excel and SPSS, revealing that students recognize the importance of understanding LOs and appreciate lecturers' efforts in facilitating this through diverse instructional strategies. The findings indicate that practical sessions, use of IT for simulations, and community-based learning are particularly effective in achieving LOs. The study underscores the critical role of aligning TMs with LOs to enhance educational outcomes and suggests that universities should prioritize professional development for lecturers and clear communication of LO to students. Future research should expand the sample to multiple institutions and explore the long-term impact of these TMs on student outcomes. These insights contribute to improving teaching practices and ensuring students acquire the necessary skills and knowledge for their future endeavours.